2014
DOI: 10.1515/revce-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the different synthetic parameters on the crystallinity and crystal size of nanosized ZSM-5 zeolite

Abstract: Effects of the different synthetic parameters on the crystallinity and crystal size of nanosized ZSM-5 zeoliteAbstract: This review aims at investigating the effect of the different synthetic parameters on the crystallinity and crystal size of nanosized ZSM-5 zeolite. The influence of the different parameters, such as the material of the synthesis source, the material ratio to each other, crystallization time and temperature, aging time and temperature, microwave treatment, seeding, and sonication, on the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 109 publications
1
20
0
Order By: Relevance
“…There are various works which studied effects of crystallization time [32][33][34][35][36][37][38]. They confirm that with increasing crystallization period, crystals grow larger.…”
Section: Crystallization Timementioning
confidence: 98%
See 1 more Smart Citation
“…There are various works which studied effects of crystallization time [32][33][34][35][36][37][38]. They confirm that with increasing crystallization period, crystals grow larger.…”
Section: Crystallization Timementioning
confidence: 98%
“…According to the literature, at very low crystallization time, only the amorphous phase is obtained. One of the impressive results of increasing crystallization time is improvement in the yield of SAPO-34 phase [32,33,35,38].…”
Section: Crystallization Timementioning
confidence: 99%
“…This could be due to the fact that silica already in the precursor may act as seeds, which could enhance the rate of crystallization. TEOS is in silane form with high reactivity, which leads to fast hydrolysis and thus results in a high rate of nucleation and crystallization , . On the other hand, colloidal silica is already in its hydrolyzed form when using LUDOX AS‐30; hence, the crystallization process could occur without hydrolysis of the silica source .…”
Section: Resultsmentioning
confidence: 99%
“…It is recognized that smaller particles of ZSM-5 zeolite are much more effective than large particles [5]. Higher resistance to coke poisoning, shorter diffusion paths and more active sites are important advantages of ZSM-5 with smaller size in catalytic reaction applications [6,7]. Therefore, CONTACT Rouein Halladj halladj@aut.ac.ir it would be interesting to develop a new approach for the synthesis of nano-sized ZSM-5 zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the factors affecting the formation of nano size zeolite crystals, such as the source of alkalinity, water content, temperature, and aging time. It has been revealed that these factors are critical on the size and uniformity of the final product [7,9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%